Evaluation of mangosteen (Garcinia mangostana) antioxidant activity in clinical trials and in vivo animal studies: A systematic review - Beatrice Elmund, Pietradewi Hartrianti (Journal of Applied Pharmaceutical Science, 2020)
Mangosteen (Garcinia mangostana), a tropical fruit highly studied because of its potent antioxidant activity, has been utilized as supplements to alleviate chronic diseases related to oxidative stress, such as cardiovascular diseases, neurodegenerative diseases, diabetes, and others. Regardless, previous studies evaluating mangosteen antioxidant activity in vivo showed conflicting results toward oxidant-related diseases, and an extensive review summarizing its antioxidant effect on oxidant-related diseases was not available. Based on these, our study aimed to systematically evaluate scientific evidence of mangosteen antioxidant activity on animal models and clinical trials regarding its role in improving oxidant-related diseases. Results showed that the administration of either mangosteen extract, isolated compound, or commercialized product was able to increase antioxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase, as well as reduce oxidative stress markers such as malondialdehyde. They were also shown to improve disease-related parameters in type II diabetes models, cardiovascular models, neurological disorder models, liver and kidney injury models, and stress-induced models. However, in clinical trials, most of the studies used commercialized mangosteen-based products that contain additional antioxidant compounds. Therefore, the results were deemed inconclusive and more clinical studies of mangosteen antioxidant activity in oxidant-related diseases are needed.
Keywords: Mangosteen, Garcinia mangostana, antioxidant, oxidative stress, clinical trials, in vivo study.